Strategi Komunikasi dalam Operasional Pelayanan pada Masa Pandemi Covid-19 - Micko Rivaldo Indrasastria; Halomoan Harahap (IPM2KPE, 2023)
This study aims to determine the extent to which the role of the public relations strategy of PT. Train Commuter Indonesia is related to the dissemination of information regarding services and operations of commuter line trains and local trains during the Covid-19 pandemic. Conducting a study to describe the implementation of PT. Kereta Commuter Indonesia during the Covid-19 pandemic, analyzed the supporting and inhibiting factors related to the implementation of this communication strategy. As well as analyzing the way of determining and implementing the Public Relations communication strategy of PT. Kereta Commuter Indonesia, and Describe the influence of the public relations strategy of PT. Train Commuter Indonesia is in operation of train trips during the Covid-19 pandemic. This study uses a qualitative method approach with interview techniques to obtain primary data from reliable and credible sources and with literature study techniques to obtain additional data on the object being studied. The results of the study show that the public relations communication strategy plays an important role in conveying information related to Commuter Train operations and services during the Covid-19 pandemic. Submission of information is carried out in two methods, namely through offline by delivering information directly and online by utilizing social media. Keywords: Commuter Line, Covid-19, Communication, Strategy, Transportation